Min house camp - Awanul Anuar, Muhammad Asyraf (Universiti Teknologi MARA, Perak, 2022)
Min House Camp is a holiday destination that is located in Kelantan. The main objective of this outcome/product is to enable Min House to revamp its marketing strategy by highlighting the main attraction at Min House Camp.